2014
DOI: 10.1186/1471-2407-14-670
|View full text |Cite
|
Sign up to set email alerts
|

Leukemoid reaction in cervical cancer: a case report and review of the literature

Abstract: BackgroundThe presentation of a leukemoid reaction in cervical cancers is rare. A leukemoid reaction is defined as leukocytosis associated with a cause outside the bone marrow, with the white blood cell count (WBC) exceeding 50*109/L. Two cervical cancers presenting with leukemoid reactions were previously reported. However, the cancers in these cases were mainly in the advanced stages and had a poor outcome.Case presentationHere we report a 40-year old patient with clinical stage (FIGO IIA1) cervical squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Nimieri et al [ 64 ] reported a case of a very aggressive metastatic cervical cancer associated with PLR (WBC 93,000/µL) and treated with chemotherapy and local radiotherapy, who died 6 weeks after the diagnosis. Qing Li et al [ 35 ] reported a case with a relatively early stage (FIGO IIA1) of cervical squamous carcinoma, which presented disease recurrence associated with LR 2 months after laparoscopic radical hysterectomy; in this case, administration of a combined chemotherapy regimen obtained an impressive tumor response with resolution of paraneoplastic LR.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nimieri et al [ 64 ] reported a case of a very aggressive metastatic cervical cancer associated with PLR (WBC 93,000/µL) and treated with chemotherapy and local radiotherapy, who died 6 weeks after the diagnosis. Qing Li et al [ 35 ] reported a case with a relatively early stage (FIGO IIA1) of cervical squamous carcinoma, which presented disease recurrence associated with LR 2 months after laparoscopic radical hysterectomy; in this case, administration of a combined chemotherapy regimen obtained an impressive tumor response with resolution of paraneoplastic LR.…”
Section: Discussionmentioning
confidence: 96%
“…The first PLR due to CST was observed in 1977 in a lung cancer patient [ 33 ]. Since then, it has been described in patients with malignant tumors of different origins [ 26 ], particularly of the cervix [ 34 , 35 ].…”
Section: Pathogenesis Of Paraneoplastic Leukocytosismentioning
confidence: 99%
“…To our knowledge, there have been only a few reported cases of EC with LR, which were mainly found in advanced stages and had a poor prognosis (13). Malignant tumors with LR typically respond poorly to chemotherapy, resulting in a short survival time for patients (14). Pretreatment thrombocytosis is associated with reduced overall survival and disease-free survival in many solid tumors, including EC.…”
Section: Discussionmentioning
confidence: 99%
“…LRs are attributed to the autoproduction of granulocyte colony stimulating factor and fever is an integral component of PLR (8). PLR is often associated with rapid tumor growth and poor clinical prognosis, although it resolves with the treatment of the underlying cancers (5).A review article covering 758 patients with solid tumours and leukocyte count over 50x10 9 /L; only 72 patients (10%) was diagnosed as PLR. Rest of the patients were detected other disorders that could cause leukocytosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…Leukemoid reaction (LR) is a reactive leukocytosis where white blood cell (WBC) count exceeds 50x10 9 /L without evidence of leukemia (4). LR is generally a benign condition and its frequency has been reported Adress for correspondence: İsmail Selvi Dr. Abdurrahman Yurtaslan Ankara Oncology Training and Research Hospital, Department of Urology 06200 Ankara -TURKEY e-mail: ismselvi33@hotmail.com Available at www.actaoncologicaturcica.com Copyright ©Ankara Onkoloji Hastanesi to range from 1% to 4% in small case series.LR has been reported in nearly all solid tumor types as a paraneoplastic syndrome and it is historically associated with poor outcomes (5).…”
Section: Introductionmentioning
confidence: 99%